Legal status of foreigners on the territory of Ukraine - Nohas, Nazar (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
In today’s globalized world, the issues of the legal status of a foreign citizen are particularly relevant. The Ukrainian state is one of the geopolitical, socio-economic and cultural and educational centers not only in the post-Soviet space, but also on a global scale. The issue of the legal status of foreigners on the territory of Ukraine became especially relevant after the full-scale invasion of Russian troops on the territory of Ukraine on February 24, 2022 and the corresponding subsequent changes to certain categories of foreign citizens. The fact of compliance with the international principle, according to which foreigners are subject to all the laws of the host country, is emphasized. This article examines the main elements of the legal status of foreign citizens residing on the territory of Ukraine. The purpose of the article is to clarify the specifics of the legal status of foreigners on the territory of Ukraine. The basic rights, duties, system of legal regulation of implementation of the legal status of foreign citizens are also considered. Changes in the legal status of citizens (in particular, Russians) following the full-scale invasion of the territory of Ukraine by Russian troops on February 24, 2022 are noted. The latest changes to the normative legal acts of Ukraine regarding the legal status of foreigners on the territory of Ukraine are characterized. The problems of the definition of "foreigners" and their classification in the scientific literature are considered. Features for distinguishing such a category in law as "foreigners" have been formulated. It is noted that the main regulatory acts of the legal status of foreigners in Ukraine are the Constitution of Ukraine, Laws of Ukraine "On the Legal Status of Foreigners and Stateless Persons", "On Immigration", "On Freedom of Movement and Free Choice of Residence in Ukraine" and other legal acts.